East Asia and Pacific Update, November 2007 : Will Resilience Overcome Risk? - World Bank (World Bank, Washington, DC, 2020)
Growth in Emerging East Asia is expected to exceed 8 percent in 2007 for a second year in succession and to moderate only slightly in 2008. Our projections for regional growth in 2007 and 2008 have been substantially increased compared to six months ago, mainly due to the unexpected and large domestic demand-led acceleration of growth in China. Growth also picked up in most of the other larger economies of the region, again a result of more buoyant investment and consumption spending. Concerns about the impact of the US sub-prime crisis and the renewed surge in oil prices have clearly increased downside risks. Nevertheless we expect that the stronger growth momentum in the region will carry through 2008. There are as yet few signs of a significant pick-up in underlying core inflation pressures or of other domestic constraints or imbalances that would require a marked slowing of growth.